2001
DOI: 10.1046/j.1523-1755.2001.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dietary oxalate to urinary oxalate excretion

Abstract: These results suggest that dietary oxalate makes a much greater contribution to urinary oxalate excretion than previously recognized, that dietary calcium influences the bioavailability of ingested oxalate, and that the absorption of dietary oxalate may be an important factor in calcium oxalate stone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
307
0
14

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 427 publications
(332 citation statements)
references
References 22 publications
11
307
0
14
Order By: Relevance
“…Indeed, increased absorption of dietary oxalate may be observed in up to one third of patients with calcium oxalate nephrolithiasis. 12 Another study found that mean oxalate absorption in normal volunteers was 8%, compared with 10.2% in a group of calcium oxalate stone formers. 26 Some data suggest that differential rates of colonization by Oxalobacter formigenes, an enteric oxalate-degrading organism, may be responsible for such variation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, increased absorption of dietary oxalate may be observed in up to one third of patients with calcium oxalate nephrolithiasis. 12 Another study found that mean oxalate absorption in normal volunteers was 8%, compared with 10.2% in a group of calcium oxalate stone formers. 26 Some data suggest that differential rates of colonization by Oxalobacter formigenes, an enteric oxalate-degrading organism, may be responsible for such variation.…”
Section: Discussionmentioning
confidence: 97%
“…The proportion of urinary oxalate that is derived from dietary oxalate is unclear: estimates range from 10 to 50%. 12 However, it is well established that a large proportion of urinary oxalate is derived from the endogenous metabolism of glycine, glycolate, hydroxyproline, and dietary vitamin C. 10,11 A recent metabolic study compared a controlled diet with 25% of protein from gelatin (2.75 g of hydroxyproline) with the same diet except with 25% of protein from whey (containing no hydroxyproline). 22 The diet that was high in hydroxyproline increased urinary oxalate excretion by 42%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from our laboratory indicates that approximately half of urinary oxalate is derived from the diet, a key environmental factor [2]. While the concentration of oxalate in urine will affect its super-saturation with calcium oxalate and thus stone growth, it is not clear what role the amount of oxalate ingested, the amount of oxalate absorbed, or the renal handling of oxalate play in stone formation.…”
Section: Introductionmentioning
confidence: 99%
“…The reason why these contradictory and confusing recommendations persisted for so long is the lack of prospective studies and the fact that analysis of oxalate remained unreliable (4) until the mid-1980s. Consequently, the amount of dietary oxalate excreted in urine and its role for renal stone formation were underestimated (5). The fact that a low-Ca diet emerged as a risk factor for Ca oxalate calculi and that a high-Ca diet emerged as a protective factor in two large epidemiologic studies (6,7) is still frequently ignored.…”
mentioning
confidence: 99%